2013
DOI: 10.1179/1362171813y.0000000122
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of thin DH36 steel plate

Abstract: A series of 4, 6 and 8 mm DH36 steel welds were produced using optimum conditions for friction stir welding (FSW). Comparator welds in the same thickness from the same plates were produced using a single sided single pass process submerged arc welds (SAW). This work was carried out to evaluate the mechanical properties of FSW material with a view to its possible application in a shipbuilding production process route. Overall, the performance of the FSW material was superior to the SAW comparators. Areas such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 4 publications
4
59
1
Order By: Relevance
“…An acicular shaped ferrite microstructure is observed in the thermo-mechanically affected zone (TMAZ), consistent over the mid-thickness of all FSW samples, whereas SAW samples present a typical acicular ferrite microstructure defined around proeutectoid ferrite grains [6]. The SAW plates present substantially more distortion than the FSW plates of the same thickness, and impact toughness levels for FSW and SAW samples are similar and within classification society impact requirements.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…An acicular shaped ferrite microstructure is observed in the thermo-mechanically affected zone (TMAZ), consistent over the mid-thickness of all FSW samples, whereas SAW samples present a typical acicular ferrite microstructure defined around proeutectoid ferrite grains [6]. The SAW plates present substantially more distortion than the FSW plates of the same thickness, and impact toughness levels for FSW and SAW samples are similar and within classification society impact requirements.…”
Section: Introductionmentioning
confidence: 87%
“…The SAW plates present substantially more distortion than the FSW plates of the same thickness, and impact toughness levels for FSW and SAW samples are similar and within classification society impact requirements. A relatively limited fatigue testing programme demonstrates that FSW samples exhibit better fatigue performance than the SAW samples of equivalent thickness [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another paper by the same authors [2] on mathematical modeling of the FSW process using computational fluid dynamics (CFD) technique, they reported that a maximum temperature of 1250°C was computed when the rotational and traverse speeds were 500 RPM and 400 mm/min, respectively. A comparison between FSW and submerged arc welding (SAW) of DH36 showed microstructure and mechanical properties improved as a [3]. Advantages of FSW of DH36 steel were also studied [4] by relating welding parameters to mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, work was initiated to establish and assess the feasibility of joining dissimilar materials using friction stir welding (FSW). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Extensive work has been carried out to demonstrate the advantages of FSW for a range of metals [24][25][26][27][28][29][30][31][32][33][34][35][36] and a growing amount of work for dissimilar alloys. 1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Results from FSW of dissimilar materials highlighted the viability of such a process with the majority of reports concluding that high quality, defect-free welds had been produced.…”
Section: Introductionmentioning
confidence: 99%